The Politics and Governance of Public Services in Developing Countries - Batley, Richard; McCourt, Willy; Mcloughlin, Claire (Taylor and Francis, 2013)
Politics and governance have become central to explanations of the widespread under-provision of public services in developing countries. Political analysis offers an understanding of what might otherwise appear to be exclusively managerial or capacity problems. The articles in this special issue of PMR contribute to three main aspects of this new literature on the political economy of service provision: how the incentives of elites are formed and affect whether, to whom and how services are provided; how top–down and bottom–up systems of accountability may act and also interact to affect incentives; and the effect of service provision on state–society relations. The analysis in this and the following articles suggests that the politics of service provision should be understood as a cycle of causation: politics affect the policy, governance and implementation of services, but in turn service provision is a theatre of politics and affects citizen formation and the development of state capacity and legitimacy. Taken as a whole, the articles suggest that a political perspective enables new insights into the causes of weak service provision, and how it can be improved.